2021
DOI: 10.3390/microorganisms9020307
|View full text |Cite
|
Sign up to set email alerts
|

Combination Regimens of Favipiravir Plus Interferon Alpha Inhibit Chikungunya Virus Replication in Clinically Relevant Human Cell Lines

Abstract: Chikungunya virus (CHIKV) is an alphavirus associated with a broad tissue tropism for which no antivirals or vaccines are approved. This study evaluated the antiviral potential of favipiravir (FAV), interferon-alpha (IFN), and ribavirin (RBV) against CHIKV as mono- and combination-therapy in cell lines that are clinically relevant to human infection. Cells derived from human connective tissue (HT-1080), neurons (SK-N-MC), and skin (HFF-1) were infected with CHIKV and treated with different concentrations of FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…First, we believed that evaluations of the EIDD-1931 antiviral effect would be most generalizable to humans if preclinical evaluations were carried out using human-derived tissues. Our previous work with nucleoside analogues has shown that antiviral activity for these agents is heavily influenced by the cell type selected for antiviral evaluations, specifically the tissue and species from which the cells are derived [ 52 , 53 ]. This specific activity is most likely due to differences in drug uptake and metabolism into the active triphosphate form, as phosphorylation kinetics of nucleoside polymerase inhibitors vary between cell types [ 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we believed that evaluations of the EIDD-1931 antiviral effect would be most generalizable to humans if preclinical evaluations were carried out using human-derived tissues. Our previous work with nucleoside analogues has shown that antiviral activity for these agents is heavily influenced by the cell type selected for antiviral evaluations, specifically the tissue and species from which the cells are derived [ 52 , 53 ]. This specific activity is most likely due to differences in drug uptake and metabolism into the active triphosphate form, as phosphorylation kinetics of nucleoside polymerase inhibitors vary between cell types [ 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work with nucleoside analogues has shown that antiviral activity for these agents is heavily influenced by the cell type selected for antiviral evaluations, specifically the tissue and species from which the cells are derived [ 52 , 53 ]. This specific activity is most likely due to differences in drug uptake and metabolism into the active triphosphate form, as phosphorylation kinetics of nucleoside polymerase inhibitors vary between cell types [ 52 , 53 , 54 , 55 ]. Second, in vitro evaluations of combination therapy are an ideal first step in both identifying and narrowing down to the most promising combinations and exposures of each drug in the combination prior to animal experimentation.…”
Section: Discussionmentioning
confidence: 99%
“…Since FAV is administered as a prodrug whose effectiveness is linked to efficient drug uptake and activation by the host cell, it is possible tissue dependent variability in these processes impacted drug effect. These considerations explain the absence of activity in HFF-1 cells, as work done in our laboratory evaluating intracellular concentrations of FAV and FAV-RTP demonstrate FAV does not effectively penetrate HFF-1 cell membranes [ 30 ], but they do not adequately explain lack of effect in HUH-7 and SK-N-MC cells. Studies investigating FAV’s antiviral potential against Zika virus (ZIKV) conducted in our lab have shown robust inhibition of ZIKV in both cell lines [ 21 ] indicating FAV uptake and activation is efficient in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous anti-DENV assays with the above-mentioned agents were conducted using Vero cells, which are often considered to be the gold standard for viral research due to their high permissivity to viral infection. Vero cells, however, are derived from the kidneys of non-human primates and may not reflect the antiviral effect that would be achieved in man, as we have previously shown that viral susceptibility to antiviral therapy is highly variable based on the host cell line employed for the investigations [ 29 , 30 ]. Here, we evaluated the antiviral candidates against DENV in multiple cell lines derived from human tissue in an attempt to maximize translation to man.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that CHIKV infection triggers the induction of type I IFNs (IFN-α and IFN-β) and IFN-γ [ 74 , 77 ]. In several cell lines infected with CHIKV, including Vero, HFF-1, HT-1080, and SK-N-MC cell lines, IFN-α dose-dependently inhibited CHIKV replication [ 78 , 79 ]. However, although IFN-α and IFN-β share an identical receptor, they have distinct mechanisms for protecting against severe CHIKV diseases [ 73 ].…”
Section: The Antiviral Ifn Responses Against Chikv Infectionmentioning
confidence: 99%